1997
DOI: 10.1074/jbc.272.36.22472
|View full text |Cite
|
Sign up to set email alerts
|

How Does Alendronate Inhibit Protein-tyrosine Phosphatases?

Abstract: Alendronate(4-amino-1-hydroxybutylidene1,1-bisphosphonate) is a drug used in the treatment of osteoporosis and other bone diseases. The inhibition of proteintyrosine phosphatases (PTPs) by alendronate suggests that PTPs may be molecular targets. As a clear understanding of the inhibition mechanism is lacking, our aim was to analyze the mechanism to provide further insight into its therapeutic effect. We show here that the inhibition of PTPs by alendronate in the presence of calcium followed first-order kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 34 publications
1
35
0
1
Order By: Relevance
“…Our results further suggest that this effect was mainly mediated by tyrosine phosphatases since vanadate showed a similar and non-additive effect to alendronate. These results are in agreement with previous observations demonstrating that alendronate inhibits protein tyrosine phosphatases Opas et al, 1997;Schmidt et al, 1996;Skorey et al, 1997). Previous data suggest that the Rho family of GTPases activate kinases that are important in cytoskeletal-mediated changes affecting motility (Mackesky and Hall, 1997;Schmitz et al, 2000).…”
Section: Discussionsupporting
confidence: 83%
“…Our results further suggest that this effect was mainly mediated by tyrosine phosphatases since vanadate showed a similar and non-additive effect to alendronate. These results are in agreement with previous observations demonstrating that alendronate inhibits protein tyrosine phosphatases Opas et al, 1997;Schmidt et al, 1996;Skorey et al, 1997). Previous data suggest that the Rho family of GTPases activate kinases that are important in cytoskeletal-mediated changes affecting motility (Mackesky and Hall, 1997;Schmitz et al, 2000).…”
Section: Discussionsupporting
confidence: 83%
“…As an example, in a recent, thorough study it was shown that addition of EDTA or catalase prevented alendronate from inhibiting PTP1B and CD45, suggesting that a combination of alendronate, trace metal ions, and H 2 O 2 was responsible for the observed timedependent PTP inhibition of alendronate (14). We, therefore, analyzed if OBA inhibited PTP1B in a time-dependent manner.…”
Section: -(Oxalylamino)-benzoic Acid 1 Is a Competitive Reversiblementioning
confidence: 99%
“…Bisphosphonates, such as alendronate, have been shown to inhibit PTPs, but their inherent affinity for bone is likely to prevent their general use in other target tissues (12). Furthermore, several of these inhibitors are time-dependent and seem to act through covalent modification of the catalytic cysteine in PTPs (13,14). The most specific inhibitors produced so far have either been phosphonates (9,15) or those based on peptides that are not suited for clinical use due to their lack of oral bioavailability and metabolic instability (reviewed in Ref.…”
mentioning
confidence: 99%
“…Indeed, when searching for PTP inhibitors, it is a common experience among laboratories that perform high throughput screenings to get high hit rates, which in many cases are caused by oxidation or alkylation of the active site cysteine (16,24). 2 Although compounds that irreversibly and/or more broadly in a time-dependent manner modify PTPs may still be useful in the clinic (25)(26)(27), structurebased optimization is often difficult, if not impossible. Hence, there is a need for development of tools that will allow structure-based design of selective inhibitors of other members of the PTP family.…”
mentioning
confidence: 99%